The risk of not receiving adjuvant chemotherapy after resection of pancreatic ductal adenocarcinoma: a nationwide analysis. Issue 2 (February 2020) - Mackay, Tara M.; Smits, F. Jasmijn; Roos, Daphne; Bonsing, Bert A.; Bosscha, Koop; Busch, Olivier R.; Creemers, Geert-Jan; van Dam, Ronald M.; van Eijck, Casper H.J.; Gerhards, Michael F.; de Groot, Jan Willem B.; Groot Koerkamp, Bas; et al.
Abstract: Background: The relation between type of postoperative complication and not receiving chemotherapy after resection of pancreatic ductal adenocarcinoma (PDAC) is unclear. The aim was to investigate which patient factors and postoperative complications were associated with not receiving adjuvant chemotherapy. Methods: Patients who underwent resection (2014–2017) for PDAC were identified from the nationwide mandatory Dutch Pancreatic Cancer Audit. The association between patient-, tumor-, center-, treatment characteristics, and the risk of not receiving adjuvant chemotherapy was analyzed with multivariable logistic regression. Results: Overall, of 1306 patients, 24% (n = 312) developed postoperative Clavien Dindo ≥3 complications. In-hospital mortality was 3.5% (n = 46). Some 433 patients (33%) did not receive adjuvant chemotherapy. Independent predictors (all p < 0.050) for not receiving adjuvant chemotherapy were older age (odds ratio (OR) 0.96), higher ECOG performance status (OR 0.57), postoperative complications (OR 0.32), especially grade B/C pancreatic fistula (OR 0.51) and post-pancreatectomy hemorrhage (OR 0.36), poor tumor differentiation grade (OR 0.62), and annual center volume of <40 pancreatoduodenectomies (OR 0.51). Conclusions: This study demonstrated that a third of patients do not receive chemotherapy after resection of PDAC. Next to higher age, worse performance status and lower annual surgical volume, this is mostly related to surgical complications, especially postoperative pancreatic fistula and post-pancreatectomy hemorrhage.